Analysis of the Relationship Between Budget Revenue and Economic Growth of Luang Namtha Province - CHEUAYTHAVONG, Phetduangchan; CHANTHAVONE, Thongphanh; XIONGTOUA, Tongvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aims to analysis the relationship between budget revenue and economic growth of Luang Namtha province, which has been collected time series data from 2011-2024, focusing the analysis for relationship as long-run correlation with Johansen's cointegretion method, short-run correlation with Vectors Error Correction Model and cause correlation with granger causality. The results of research: The long-run correlation shows that the coefficient is positive and rejected null hypothesis () with a statistical significance level of 0.01, which means that budget revenue (R) and economic growth of Luang Namtha province (GDP) have a positive long-run relationship. When budget revenue increases, it will effect on the long-run on economic growth of Luang Namtha province increases. On the contrary, if budget revenue decreases, it will affect to the long-term economic growth of Luang Namtha province decreases with a confidence level of 99%. The short-run correlation is show that for the GDP is dependence variable, it is accepted null hypothesis () with statistical significant level of 0.1 and coefficient is a negative value, this show that the economic growth of Luang Namtha province and budget revenue are related in the short run. For budget revenue (R) is dependence variable show that it is not related in the short-run. Because, the value of coefficient is positive and accepted null hypothesis (). The results of the causality test between budget revenue (R) and economic growth of Luang Namtha province (GDP) show that the R does not granger cause GDP, there are accepted null hypothesis this means that R does not Cause GDP. For the case GDP does not granger cause R, there are rejected null hypothesis with a significance level of 0.05, which means that budget revenue has granger cause on the economic growth of the Luang Namtha province.